Analisis Hak Korban Korban Kekerasan Seksual dalam Rancangan Undang-Undang Penghapusan Kekerasan Seksual dalam Perspektif Hukum Positif dan Hukum Islam - Susiana Kifli; Atika Ismail (Wajah Hukum, 2022)
The consideration and protection of the interests of victims of sexual abuse, whether through the legal process or through specific social care facilities, must be taken into account in criminal law policies and social policies, both state power institutions and existing social institutions. Based on the goals and obligations of the state to achieve an equitable distribution of justice for the sake of everyone, the rights of sexual assault victims to be protected are a crucial part of human rights in the domain of social security. three tiers: local, regional, and global. The way that Indonesian criminal law protects sexual assault victims legally in order to stop victimization. The form of giving victims of sexual assault legal protection is general legal protection, Ini termasuk membuat restitusi dan memberikan imbalan. menawarkan konseling sebagai akibat munculnya efek psikologis yang merugikan dari kejahatan, memperoleh dukungan hukum, dan mengamankan layanan bantuan medis bagi korban yang menderita secara fisik akibat kejahatan. Salah satu bentuk dukungan bagi korban kejahatan adalah bantuan hukum. Hukum Islam mengklasifikasikan pemerkosaan sebagai perzinahan dengan paksaan (al-wath'u nil-kikrah), dan mereka yang melakukannya berisiko menghadapi hukuman berat (had). The crime of decency or adultery serves as the act's foundation.